Mountain Pastoralism 1500–2000: An Introduction. (30th November 2009) - Montero, Raquel Gil; Mathieu, Jon; Singh, Chetan
Abstract : This special issue of Nomadic Peoples presents a collection of articles that give an idea of the continuities and changes of pastoralism in upland areas during the past five centuries. They are the result of a lengthy project on 'Mountain Pastoralism and Modernity' organized by historians from different continents. The following introduction aims to trace the framework of that enterprise. It takes up a few key concepts: mountain pastoralism, history, verticality, intensification and mobility. It then describes the project, outlines the current state of research in the continents concerned, and points to some results and prospects.